Shaping Healthy Beginnings: A Systematic Review on the Impact of Parenting Styles on Toddler Nutritional Status - Sofiatun; Deviantony, Fitrio (KHD-Production, 2024)
Toddlers need a sufficient diet to support their physical and mental development because they grow and develop quickly during this time. Children under five's nutritional status is crucial to their overall health. A child's nutritional health is also influenced by their parents' educational methods and parenting styles. While ineffective parenting can lead to nutritional issues, effective parenting can help children get the nutrition they need. This study investigates how parenting practices affect the nutritional status of children under five. A review of the literature from 2019 to 2020 was conducted as part of this research technique using Google Scholar and the keywords